Keeping fit in your 50s. Strength [videorecording (DVD)] : workout essentials for a changing body - Trimble, Skye (Acorn Media, 2003)
Muscle is the body's natural heating system. Regular strength training revs up your metabolism and helps protect against the bone loss that naturally occur in your 50s. A complete strength workout includes insights into the importance of strength training; exercise tips for achieving maximum goals; 40-minute core routine, including abdominal section; advanced exercises; Q & A session.